CBMT-38. THERAPEUTIC INHIBITION OF THE SPLICEOSOME IN GLIOBLASTOMA: CHANGES FORM MINOR TO MAJOR. (11th November 2019) - Bonifert, Tobias; Arora, Sonali; Fitzgibbon, Matthew; Paddison, Patrick
Abstract: Chemical or genetic perturbation of the spliceosome function may represent a therapeutic opportunity for Glioblastoma multiforme (GBM) and other cancers. We and others have shown that oncogenic MYC activity causes spliceosome vulnerability and leads to deficits in 3' splice site recognition upon spliceosome perturbation. Several spliceosome inhibitors in pre-clinical development and in clinical trials target the U2 snRNP subcomplex SF3B, which is essential for 3' splice site recognition. We showed that knockdown of one of its subunits, PHF5A, causes GBM-specific changes in splicing, including increases in exon skipping, intron retention and activation of alternative 3' and 5' splice sites. However, in depth analysis of these events revealed they are disproportionately enriched for "minor" introns. This class of ~800 introns is specifically excised by an alternative splicing pathway which involves the U12-dependent spliceosome. Remarkably, we provide evidence that inhibition of PHF5A in GBM stem-like cells causes increased retention of most minor introns, as well as activation of cryptic and alternative U2 snRNP-dependent splicing sites. We further demonstrate that components of the U12 snRNP complex are differentially required for GSC-specific viability. Our results suggest that regulation of the splicing of U12-type introns may be critically important for GBM tumor cell viability.